The holocene- and upper pleistocene pollen record from Padul (Granada, Spain): A new study - Pons, A; REILLE, M (Palaeogeography, Palaeoclimatology, Palaeoecology, 1988)
Two borings were made at the site of Padul (Granada). Pollen analysis of 200 spectra from two successive sequences, 14.8 and 8 m deep, enables a description of the vegetational and climatic history of this region, the most southern one in Europe, from Early Würmian times. The chronology is supported by twenty-one 14C dates. Original equivalents are found for the great European Prewürm interstadials. A markedly arid though thermically not extreme episode, exactly equivalent to stage 4 of the marine isotopic stratigraphy, closes this relatively temperate period. The middle part of the Last Glacial shows climatic fluctuations that are poorly characterized, as is often the case in Europe for this period. A long section, very probably corresponding to the complete Last Pleniglacial, does not show any climatic amelioration. Towards 15,000 yr B.P. a change in the diagram is noted that can only be interpreted as reflecting a larger expansion of a regional steppe cover. This event, also reported on three occasions in southeast France, marks the beginning of the Oldest Dryas. The climatic amelioration of ca. 13,000 yr B.P. is far more pronounced here than anywhere else in Europe, whereas that at 10,000 yr B.P. is not so clearly marked. This unexpected result may be accounted for by the fact that Padul is the first continental site so far south and so near Pleniglacial refuges to be known: on the other hand, this result is consistent with what is known from oceanic isotopic stratigraphy. A quite new late-glacial and Holocene vegetational history is revealed, characterized by the early appearance and dominance of Quercus ilex oak forests of a southern type and the early occurrence of Quercus suber and Olea: it is the first account of a complete history of the postglacial reafforestation in a region with a modern semi-arid mediterranean climate. From the palaeoclimatic point of view, it shows that the hot and humid Holocene optimum was attained slightly before 8000 yr B.P. and that the Holocene climatic fluctuations were of but small amplitude.
Keywords: climatic fluctuations; Holocene; Padul; Pollen analysis; vegetation history (PG)